Madagascar : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2003)
This report summarizes the improved Intermediate Poverty Reduction Strategy Paper (PRSP) of Madagascar, and the new policy orientation of the government. This strategy is based on an objective analysis and precise criteria. It presents the general framework of intervention of the PRSP and an analysis of poverty. It defines the strategies of the fight against poverty, and provides overall objectives and actions to be implemented. It reviews the cost and the financing of the programs and also describes the monitoring and evaluation methods of the poverty reduction strategy.